2021
DOI: 10.1002/anie.202106215
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Avoid Artifacts in Mass Spectrometry‐Based Epitranscriptome Analyses

Abstract: In this report, we perform structure validation of recently reported RNA phosphorothioate (PT) modifications, a new set of epitranscriptome marks found in bacteria and eukaryotes including humans. By comparing synthetic PT‐containing diribonucleotides with native species in RNA hydrolysates by high‐resolution mass spectrometry (MS), metabolic stable isotope labeling, and PT‐specific iodine‐desulfurization, we disprove the existence of PTs in RNA from E. coli, S. cerevisiae, human cell lines, and mouse brain. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Further, our data suggest that ALKBH1 can install f 5 C on polyadenylated RNA. Notably, while bulk poly(A)RNA fractions can be contaminated with modified nucleosides from more abundant RNA species 35 , given the low levels of f 5 C in total RNA and the purity of our poly(A) fraction (Supplementary Fig. 19 ), we believe that the observed modification levels are unlikely to have originated from non-poly(A)RNAs.…”
Section: Resultsmentioning
confidence: 89%
“…Further, our data suggest that ALKBH1 can install f 5 C on polyadenylated RNA. Notably, while bulk poly(A)RNA fractions can be contaminated with modified nucleosides from more abundant RNA species 35 , given the low levels of f 5 C in total RNA and the purity of our poly(A) fraction (Supplementary Fig. 19 ), we believe that the observed modification levels are unlikely to have originated from non-poly(A)RNAs.…”
Section: Resultsmentioning
confidence: 89%
“…Through -omics methodology, MS can provide these data via high throughput technologies for larger RNAs as well as heterogeneous biological samples (cell lysates, etc.) [ 112 , 113 , 114 ]. Additionally, advances have been made in native MS to provide tertiary contact information as well as the stability of certain folded RNAs [ 115 , 116 , 117 , 118 ].…”
Section: Experiments That Can Help Validate MD Simulation Resultsmentioning
confidence: 99%
“…Systematic and careful studies have also revealed the potential pitfalls and provided guidelines for avoiding them. [34,19,35,36] For prokaryotes, the number of studies is currently small, but given the potential of the epitranscriptome for bacterial fitness, stress adaptation and thus human health in the context of bacterial infection, more studies will follow. Therefore, we set out to systematically test different methods for mRNA preparation using the model bacterium E. coli MG1655.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in the analysis of RNA modifications by sequencing and mass spectrometry have led to an ever‐rising number of studies focusing on the molecular mechanism of mRNA modifications in eukaryotes. Systematic and careful studies have also revealed the potential pitfalls and provided guidelines for avoiding them [34,19,35,36] . For prokaryotes, the number of studies is currently small, but given the potential of the epitranscriptome for bacterial fitness, stress adaptation and thus human health in the context of bacterial infection, more studies will follow.…”
Section: Discussionmentioning
confidence: 99%